Peran Single Mother Terhadap Penanganan Kebohongan Anak Melalui Komunikasi Interpersonal Perspektif Hukum Islam - Khasib Batunnikmah (AL-HUKAMA, 2020)
The role of parents is very important in building a child's personality. It becomes not easy when the role is only carried out by a single mother. This article aims to examine how the effects of interpersonal communication is done by singgle mother to change the attitudes of children. The importance of doing interpersonal communication is then seen also using nass. The study was conducted on two single mother informants and their children using interview and observation methods. One of the single mother informants became the single mother because of a divorce and the other because her husband passed away. They both chose to raise their children themselves so they had to play a dual role in the family. They become mothers as well as the breadwinners of the family. This fact raises deception, which is the act of avoiding hurting others by lying, between mother and child. The existence of interpersonal communication can then minimize the existence of deceptions in the communication process which can affect the relationship between parents and children.